Economic crisis, fiscal austerity policy, and health expenditure in Brazilian municipalities: A time series analysis - Debora Castanheira; Monica Campos; Isabel Emmerick (Social Sciences and Humanities Open, 2025)
In 2016, the Brazilian government officially established a Fiscal Austerity Policy (FAP) with the Constitutional Amendment 95 (CA95). The FAP's impact on health expenditures in Brazilian cities is still uncertain, as the effects of cuts in expenses have not been measured. This article aims to determine the point at which public health spending began to decline, signaling the onset of the fiscal austerity policy's impact on the health sector in Brazil, by analyzing both the behavior of federal health resource transfers to municipalities and the municipalities' own health expenditures. We use time-series data regression methods to analyze trends in municipal health expenditure and the Brazilian GDP from 2002 to 2019. Data was compiled from the Information System on Public Health Budgets. Cities were classified based on population size. The effects of the CA95 were estimated using two time segments: before CA95 (2002–2016) and post-CA95 (2017–2019). We performed joinpoint regressions to identify other health expenditure trends unrelated to CA95. The ITS regression model shows continuous growth in health expenditure by all financing sources from 2002 to 2016, regardless of size. Post-CA95, there is no significant alteration. Joinpoint regressions show that health expenditures tended to increase from 2002 to 2014, with little difference by size. After 2014, there was a downward trend, with a slight recovery after 2017. The downward trend of health expenditures begins two years after the downward trend in GDP per capita. The ratio of health expenditures as a percentage of GDP shows a deceleration of investments in two periods: 2008–2011 and 2015–2019. ITS models didn't show the expected effects ofCA95. The joinpoint models showed that FAP for health started in 2014, not with CA95. This result allows more sensitive analyses of the FAP's effects on Brazil's health. The study shows that, unlike after 2014, previous periods of economic slowdown did not lead to reduced health investment, suggesting that the decline was a political choice rather than an inevitable consequence of the crisis.